2016
DOI: 10.1016/j.jjcc.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of red blood cell distribution width during hospitalization predicts mortality in patients with acute decompensated heart failure

Abstract: These data document that the change in RDW values during hospitalization independently predicts poor outcomes in patients with ADHF. Continuous follow-up of RDW values could provide useful information for long-term prognosis after heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 27 publications
(31 reference statements)
1
46
0
Order By: Relevance
“…To further support the clinical significance of RDW in HF patients, Nishizaki et al evaluated 160 patients who died as a result of HF and found that RDW >16.5% was significantly associated with fatal HF . Uemura et al measured RDW at the time of hospital admission and during hospitalization in patients with acute decompensated HF and reported that the alteration in RDW level during hospital stay, can predict adverse outcomes and all‐cause death among patients . The results of a meta‐analysis of 18,288 HF patients showed that level of RDW on admission and discharge, as well as its variation during treatment, can be used as marker to predict prognosis of HF.…”
Section: Prognostic and Diagnostic Value Of Rdw In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…To further support the clinical significance of RDW in HF patients, Nishizaki et al evaluated 160 patients who died as a result of HF and found that RDW >16.5% was significantly associated with fatal HF . Uemura et al measured RDW at the time of hospital admission and during hospitalization in patients with acute decompensated HF and reported that the alteration in RDW level during hospital stay, can predict adverse outcomes and all‐cause death among patients . The results of a meta‐analysis of 18,288 HF patients showed that level of RDW on admission and discharge, as well as its variation during treatment, can be used as marker to predict prognosis of HF.…”
Section: Prognostic and Diagnostic Value Of Rdw In Heart Failurementioning
confidence: 99%
“…59 Uemura et al measured RDW at the time of hospital admission and during hospitalization in patients with acute decompensated HF and reported that the alteration in RDW level during hospital stay, can predict adverse outcomes and all-cause death among patients. 60 The results of a meta-analysis of 18,288 HF patients showed that level of RDW on admission and discharge, as well as its variation during treatment, can be used as marker to predict prognosis of HF. This meta-analysis also revealed that HF patients with higher RDW had poorer prognosis.…”
Section: Prognostic and Diagnostic Value Of Rdw In Heart Failurementioning
confidence: 99%
“…[2][3][4] It has been shown that there is a strong relationship between RDW and mortality, regardless of anemia, in most cardiovascular and other diseases. [9][10][11][12][13][14][15] High baseline RDW levels are related to increased mortality in acute pulmonary embolism (APE) but there is no data to determine whether increasing RDW levels in APE has more prognostic value than a single measurement. [9][10][11][12][13][14][15] High baseline RDW levels are related to increased mortality in acute pulmonary embolism (APE) but there is no data to determine whether increasing RDW levels in APE has more prognostic value than a single measurement.…”
Section: Introductionmentioning
confidence: 99%
“…5-8 Furthermore, RDW levels that increase or remain high during hospitalization are considered better predictors than a single measurement. [9][10][11][12][13][14][15] High baseline RDW levels are related to increased mortality in acute pulmonary embolism (APE) but there is no data to determine whether increasing RDW levels in APE has more prognostic value than a single measurement. 16 In Clin Respir J.…”
mentioning
confidence: 99%
“…RDW was shown to be an important prognostic indicator in various conditions, such as patients with severe sepsis and septic shock,[23] critically ill,[24] heart failure,[567] acute myocardial infarction,[89] and those undergoing cardiac catheterization. [10] The prognostic significance of RDW in internal medicine, newly hospitalized patients, and all-cause mortality was also explored.…”
Section: Introductionmentioning
confidence: 99%